If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(10 + -1x) = 32 (10 * -9 + -1x * -9) = 32 (-90 + 9x) = 32 Solving -90 + 9x = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '90' to each side of the equation. -90 + 90 + 9x = 32 + 90 Combine like terms: -90 + 90 = 0 0 + 9x = 32 + 90 9x = 32 + 90 Combine like terms: 32 + 90 = 122 9x = 122 Divide each side by '9'. x = 13.55555556 Simplifying x = 13.55555556
| -3x+(-2)=-16 | | b^2+3b=40 | | -6xy+xy= | | 21=-3+8x | | 3(15-6)+(18-12)= | | 0.1x-0.6x-6=19 | | 2y-10y= | | 3=16x-20x^2 | | 4x-5=7+2x | | 3(4x+1)+2(1-5x)= | | X+2x+(-5)=-11 | | V=x(16-2x)(14-2x) | | 3(15-6)+(18-144)= | | 45=x(14-x) | | 3(s)=18 | | 2(x+1)(x-3)-(x+1)=0 | | x(x-6)-27=0 | | h=100t-16t^2 | | 2(2x+3)+1=11 | | 34(2*3)+45= | | -2f+3-2f-8= | | -2f+3-2f-8=-4f-5 | | 9.1x-6.5=x+2.7 | | 5(3-4y)=20 | | 12y-y+3= | | 11-2t=1 | | 5(y+4)=3 | | 7p+19=-2+55 | | 3s+2=-62 | | 6(x+2)-5=2x+4(2+x) | | 3y-1=32 | | 3x+25=4x |